Telecommunications Tower Kits Manufacturing Model Based on Ikea’s Approach to Minimize the Return Due to Missing Parts in a Metalworking Enterprise Kit - Lavado, Katia (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.